The Effect of High Intensity Interval Training on Running Speed of Extracurricular Futsal Participants in Sman 5 Malang. - jannah, nurul kholifatul; Yunus, Mahmud (Journal of Strength and Conditioning, 2024)
This study aims to provide a High Intensity Interval Training program and determine whether the training affects the speed of futsal extracurricular participants at SMAN 5 Malang. This study uses a quantitative approach with an experimental method. In this case, the design used is a one-group pre-test and post-test design. This method was chosen because the researcher wanted to evaluate how High Intensity Interval Training (HIIT) carried out for 16 sessions affects the speed of futsal extracurricular participants at SMAN 5 Malang. Before receiving treatment, the subjects will undergo a pre-test first. Then the subjects carry out the High Intensity Interval Training (HIIT) program and end with a post-test. Pre-test and post-test measurements are carried out with a 30-meter sprint run test and time is taken using a stopwatch. The results of this study indicate that there is an effect of High Intensity Interval Training on running speed in futsal extracurricular participants at SMAN 5 Malang.